THE STRATEGIES OF EFL TEACHERS TO INTEGRATE ISLAMIC VALUES IN TEACHING ENGLISH AT ENGLISH DEPARMENT OF IAIN MADURA - Dian Fajariyah Damayanti; Junaidi Mistar; Mutmainnah Mustofa; Dzul Fikri (Graduate Program, University of Islam Malang, 2022)
Strategy is the way how the teacher achieves the goal based on the objective of teaching or depend on the class and students’ need. English department whose science is secular and non religious must deal with the vision and mission of IAIN Madura which is religious and competitive. The researchers uses basic qualitative studies. The aim of this study is to identify the teaching strategies and how the English teachers of IAIN Madura integrate the Islamic value into their teaching. Teacher 1 used brainstorming in teaching English. Teacher 2 used demonstration or games in teaching English. Teacher 3 case-based small group discussion strategy in teaching English, while teacher 4 usually used case-based small group discussion strategy. Holistic integration was done by teacher 2who used the text of Islam in teaching reading and teacher 3 also used the Islamic audio in teaching listening. While teacher 1 puts the Islamic values in the evaluation. But the teacher 4 did not put Islamic values in the material. The specific integration was done by teacher 1, 2, 3 and 4. They always try to exemplify with a good attitudes and moral values as shown when the teacher always implement honesty, good attitude, patience, and others in teaching learning process. The researcher found that all teachers apply curriculum approach, namely context-fictional approach, the lecturers replace greeting with Assalamualaikum and pray or say Basmalah before and at the end of the teaching and learning.